Evaluation of Drug Procurement Policy on Health Administration and Drug Demand at Lubuk Pakam Community Health Center - Meirizal Jefrinaldi; Romauli Anna Teresia Marbun; Basyariah Lubis (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: Drug availability is an important indicator in ensuring service continuity and the quality of primary healthcare facilities. An effective drug management system can improve community access to medicines through the strengthening of primary healthcare services. Accurate needs planning, stock control, and procurement processes are key factors in maintaining the continuity of healthcare services. This study aimed to evaluate the drug procurement policy in relation to health administration and drug demand at Lubuk Pakam Public Health Center.  Methods: This study employed a qualitative approach with a descriptive evaluative design. Data were collected through in-depth interviews, observation, and document review. The main informants consisted of the Head of the Public Health Center, the responsible pharmacist, and a pharmaceutical management officer (TTK). Triangulation informants included the treasurer, e-logistics system officer (SIMO), and a nurse.  Results: The findings showed that drug procurement had been implemented relatively well and systematically through the stages of planning, submission through SIMO, distribution, recording, and periodic evaluation. Coordination among staff was carried out through routine meetings and internal communication, which supported stock monitoring and the handling of drug needs. The SIMO system facilitated recording and drug needs planning, although technical obstacles such as network disruptions and slow synchronization were still encountered. Other challenges included budget limitations, delayed fund disbursement, delayed distribution, discrepancies between requested and received medicines, and differences between physical stock and system data. Drug availability greatly influenced service quality, and when shortages occurred, drug substitution was carried out based on pharmacist recommendations.  Conclusion: The drug procurement policy at Lubuk Pakam Public Health Center has had a positive impact on health administration and the fulfillment of drug needs. However, improvements are still needed in procurement flexibility, acceleration of financial administration, supply accuracy, and the reliability of the e-logistics system to further optimize healthcare service quality.